Healthcare data analytics and management - Dey, Nilanjan 1984-; Ashour, Amira 1975-; Bhatt, Chintan M. 1988-; Fong, Simon James (Advances in ubiquitous sensing applications for healthcare, 2019)
Healthcare Data Analytics and Management help readers disseminate cutting-edge research that delivers insights into the analytic tools, opportunities, novel strategies, techniques and challenges for handling big data, data analytics and management in healthcare. As the rapidly expanding and heterogeneous nature of healthcare data poses challenges for big data analytics, this book targets researchers and bioengineers from areas of machine learning, data mining, data management, and healthcare providers, along with clinical researchers and physicians who are interested in the management and analysis of healthcare data